2010
DOI: 10.1097/ta.0b013e3181efbed9
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of Surgical Services in Central Florida: The Next Step in Acute Care Surgery

Abstract: Regionalization of ACS to TCs is a viable option from a business perspective. Access to care is preserved during an approaching crisis in emergency general surgical coverage. The referring hospital is relieved of an unfavorable payer mix and surgeon call problems. The TC receives a new revenue stream with limited impact on resources by absorbing these patients under its fixed costs, saving the CH variable costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…In several jurisdictions in North America and the United Kingdom, these findings have contributed to the regionalization of care into specialized centers. [61][62][63] In the current study, we found that patients who had their operation performed by surgeon with annual volumes ≤35 procedures a year were more likely to be frail, live in rural areas, and receive their hip replacements from lower volume hospitals. This patient profile is consistent with previous descriptions of patients who utilize lower volume centers.…”
Section: Principal Findingsmentioning
confidence: 52%
“…In several jurisdictions in North America and the United Kingdom, these findings have contributed to the regionalization of care into specialized centers. [61][62][63] In the current study, we found that patients who had their operation performed by surgeon with annual volumes ≤35 procedures a year were more likely to be frail, live in rural areas, and receive their hip replacements from lower volume hospitals. This patient profile is consistent with previous descriptions of patients who utilize lower volume centers.…”
Section: Principal Findingsmentioning
confidence: 52%
“…Still, few of our respondents addressed this larger structural issue, even though others have written about regionalizing care for NTSEs, much like has been done for trauma as a result of policy initiatives [3638]. In contrast, our respondents frequently referred to tension between acute care and community based general surgeons sharing the same patient population as a threat to the future of ACS.…”
Section: Discussionmentioning
confidence: 94%
“…Depending on size, location, and practice setting, it may make sense from a quality and cost perspective to regionalize the care of EGS patients to centers with routine availability of dedicated EGS structures and processes. 32-34 In fact, that the proportion of EGS patients presenting in transfer was higher in ACS models, suggests that this phenomenon may already be occurring to a certain extent.…”
Section: Discussionmentioning
confidence: 99%